Development of Oral Cancer : Risk Factors and Prevention Strategies - Al Moustafa, Ala-Eddin (Springer International Publishing : Imprint: Springer, 2017)
This book aims to provide the reader with a complete understanding of the development of oral cancer by explaining the role of a wide variety of implicated risk factors and identifying their gene targets and key regulators. Some of the discussed risk factors are well known, including smoking, alcohol, betel quid chewing, and oncoviruses such as high-risk human papillomaviruses and Epstein-Barr virus; however, careful attention is also paid to less widely recognized factors, such as Qat chewing and yerba Mate consumption. The book concludes by describing and evaluating the most important strategies currently available for the prevention of oral carcinogenesis in humans. In presenting the most up-todate research and knowledge on these topics, this book will serve as a valuable source of up-to-date information for oncologists, cancer scientists, and medical students.
Keywords: Dentistry.; Medicine.; Cancer research.; Oncology.; elektronické knihy; electronic books